Morphophonemic Rules of The Tontemboan Makala’i Dialect in Minahasa: a Form of Regional Language Preservation - Piri, Elvie Nitje; Rattu, Jultje Aneke; Moniung, Ilke Janemralina (SAWERIGADING, 2025)
This study observes and finds the process of sound changes (morphophonemics) in the Tontemboan Language (BT) Makala’i dialect which is rarely found in this era of globalization, even threatened with extinction. The aim is to describe sound changes which are the result of morpheme meetings in the formation of words and phrases. Based on qualitative data obtained through surveys, recordings of sermon content, and direct interviews with the community in Taraitak Village, Langowan District, Minahasa Regency, North Sulawesi. Using Crystal's theory for the morphophonemic process combined with Nida's theory and the theories of Alwi, Sumadi and Ramlan. Based on the qualitative data obtained, it shows that the discovery of morphophonemic forms in the BT Makala’i dialect consists of: 1) sound changes, /N/ then, /N/ in the particle aN. Variations in /N/ changes depend on the initial phoneme conditions of the basic form or the word it is attached to. Other phoneme changes also occur in /w/ to /b/, /r/ to /d/ if these sounds are in the initial position. 2) The addition of sound occurs in the second part of the basic form with the initial phoneme of the vowel that undergoes the process of mǝN-+R. The meeting between /a/ and /a/, the meeting between /i/ and /a/, and the meeting between /u/ and /a/. 3) The loss of phoneme sound occurs in /N/ which is found in the affixes maN-, pᵞaN-, paN—an, mǝN—an, mǝN-+R when combined with the basic form with the initial phoneme /l/. /m/, /n/, are also found in the basic form with the initial phonemes /p/, /w/, and /t/. The morphophonemic rules of the Tontemboan language show complexity but have order and system. AbstrakStudi ini mengamati dan menemukan proses perubahan bunyi (morfofonemik) dalam Bahasa Tontemboan (BT) dialek Makala’i yang jarang ditemukan di era globalisasi ini, bahkan terancam punah. Tujuannya adalah untuk mendeskripsikan perubahan bunyi yang merupakan hasil pertemuan morfem dalam pembentukan kata dan frasa. Berdasarkan data kualitatif yang diperoleh melalui survei, rekaman isi khotbah, dan wawancara langsung dengan masyarakat di Desa Taraitak, Kecamatan Langowan, Kabupaten Minahasa, Sulawesi Utara. Menggunakan teori Kristal untuk proses morfofonemik yang dikombinasikan dengan teori Nida dan teori Alwi, Sumadi, dan Ramlan. Berdasarkan data kualitatif yang diperoleh, menunjukkan bahwa penemuan bentuk morfofonemik dalam BT dialek Makala’i terdiri dari: 1) perubahan bunyi, /N/ kemudian, /N/ dalam partikel aN. Variasi perubahan /N/ bergantung pada kondisi fonem awal bentuk dasar atau kata yang melekat padanya. Perubahan fonem lainnya juga terjadi pada /w/ menjadi /b/, /r/ menjadi /d/ jika bunyi-bunyi ini berada di posisi awal. 2) Penambahan bunyi terjadi pada bagian kedua bentuk dasar dengan fonem awal vokal yang mengalami proses mǝN-+R. Pertemuan antara /a/ dan /a/, pertemuan antara /i/ dan /a/, dan pertemuan antara /u/ dan /a/. 3) Hilangnya bunyi fonem terjadi pada /N/ yang ditemukan pada imbuhan maN-, pᵞaN-, paN—an, mǝN—an, mǝN-+R ketika dikombinasikan dengan bentuk dasar dengan fonem awal /l/. /m/, /n/, juga ditemukan dalam bentuk dasar dengan fonem awal /p/, /w/, dan /t/. Aturan morfofonemik bahasa Tontemboan menunjukkan kompleksitas tetapi memiliki keteraturan dan sistem.